Analisis Peran Pemuda dalam Pemberdayaan Usaha Mikro Kecil Menengah (UMKM) Berbasis Destiasi Wisata: Studi kasus di Desa Serang Kecamatan Panggungrejo Kabupaten Blitar - Alfiani, Dwi Analta; Said, M. Mas'ud; Kurniati, Rini Rahayu (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Blitar Regency has good potential in the fields of tourism and MSMEs, if managed properly it can improve community welfare. However, youth in Blitar Regency have not been able to fully develop this potential, due to several inhibiting factors, so they do not actively participate in managing regional potential, and many prefer to work outside the region. Through a descriptive qualitative approach, the author analyzes the diversity of youth characters in Blitar Regency, focusing on the role of youth in managing and developing regional potential through tourist destinations and MSMEs. Data collection uses Interview, Observation, and Documentation methods. The data will be analyzed using the Miles Huberman model. The validity of the data is tested through a credibility test using triangulation (technique, source, and time), as well as a transferability test to show the degree of accuracy so that it can be applied by the region to form the character of youth who are enthusiastic in managing the potential of the region. There are five roles of youth in community empowerment through the tourism sector and MSMEs that can be applied in Blitar Regency. Empowerment through youth requires local government participation to support and facilitate the active movements of youth in developing regional potential, besides that youth must dare to be the pioneers of renewal.